Women in the triathlon - the differences between female and male triathletes: a narrative review - Loosli, M.; Nikolaidis, P. T.; Scheer, V.; Wilhelm, M.; Forte, P.; Andrade, M.; Rosemann, T.; Duric, S.; Cuk, I.; Knechtle, B. (Frontiers in Sports and Active Living, 2025)
Introduction: Triathlon events have gained popularity in recent years. With the increasing participation of women, aspects that influence performance and physiology, as well as differences between women and men, are of interest to athletes and coaches. A review of the existing literature concerning differences between women and men in triathlon is lacking. Therefore, this narrative review aimed to compare female and male triathletes in terms of participation, performance, and the different influences on performance (e.g., physiology, age, pacing, motivation).